Використання новітніх логістичних технологій для оптимізації діяльності сучасних підприємств - Слюсар, А. П.; Хрустальова, С. В. (ХНУРЕ, 2024)
The article demonstrates the relevance of modern technologies and examines innovative logistics as the most relevant component of enterprise logistics activities. The essence of the technologies is revealed, and the advantages and peculiarities of their implementation in real-time conditions are described. The most progressive innovative technologies in the logistics sphere are identified, which will enable all participants in the logistics chain to create a transparent and efficient system for recording transactions, asset tracking, and managing all associated documents. It is proven that the application of progressive innovations can ensure the growth of efficiency in flow processes, reduction of total costs for their implementation, and improvement in the quality of consumer service overall.
Keywords: логістичні технології; AGV (AutomatedGuidedVehicle); коллаборативні роботи; комплексна автоматизація; цифрові двійники; Інтернет речей; RFID; складська логістика; промислова логістика